Bilateral Vitreopapillary Traction Demonstrated by Optical Coherence Tomography Mistaken for Papilledema. (4th October 2012) - Houle, Elizabeth; Miller, Neil R.
Abstract : Purpose . The purpose of this study was to report a case of bilateral vitreopapillary traction, previously misdiagnosed as papilledema. Methods . A case report is presented of a 47-year-old woman with a prior diagnosis of papilledema, who is shown to have bilateral vitreopapillary traction rather than true optic disc swelling, confirmed by optical coherence tomography (OCT). Results . OCT showed vitreous traction surrounding the optic discs of both eyes. Fluorescein angiography demonstrated focal leakage of both discs. Conclusion . Bilateral disc elevation caused by vitreous traction can be confused with papilledema. In such cases, OCT can be used to arrive at the correct diagnosis. Although the phenomenon of vitreopapillary traction is well reported, this case indicates that not all ophthalmologists recognize the condition.